PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (Studi Pada PT. BPR Arta Utama Pekalongan) - Gita S.P., Robertus; Yuniawan, Ahyar (Diponegoro Journal of Management, 2016)
The purpose of this research is to analyze further the effect of transformational leadership style, employee motivation, and organizational culture on employee performance. In this study, the researcher uses of transformational leadership style, work motivation, and organizational culture as an independent variables and employee performance as the dependent variable. Methods of data collection in the research that is used is a questionnaire with a sample of 57 permanent employees of PT. BPR Arta Utama Pekalongan (consisting of a central office and four branch offices), in which the research is using a sample of census or using the entire population of employees of PT. BPR Arta Utama. Methods of data analysis used in this research is multiple linear regression analysis.Based on the multiple linear regression that is performed to produce transformational leadership style, it has a positive and significant impacts on employee performance. Meanwhile, work motivation and organizational culture do not affect the performance of employee.